Value of off-season fresh Camellia sinensis leaves. Antiradical activity, total phenolics content and catechin profiles - Baptista, José (2022)
“Normal-season” (bud plus first two leaves processed as commercial tea between Apr–Sep), “unused” (remaining leaves collected in Sep and Apr) and “off-season” (all leaves collected between Sep-Apr) green tea leaves samples from Camellia sinensis were extracted by water infusion followed by solvent–solvent partition to recover catechins, that were separated and quantified by HPLC methods. Total catechins content ranged between 23.72 and 73.61 mg/g of the dry weight (DW) leaves for the off-season samples and was 97.51, 115.12 and 184.62 mg/g DW for Apr, Sep and normal-season samples, respectively. The free radical scavenging activity of the off-season samples ranged between 45 and 80%, 79-90% and 90-92% for the 25, 50 and 100 ppm concentrations, respectively, after 20-min reaction time. The other samples presented values of 87%, 91% and 94% (Sep), 88%, 92% and 93% (Apr) and 89%, 93% and 95% (normal-season), using the same conditions. Total phenolics content ranged between 43.21 and 139.02 mg of gallic acid equivalents (GAE)/g DW for the off-season samples and was 182.23, 216.05 and 221.32 mg of GAE/g DW for Apr, Sep and normal-season samples, respectively. Results revealed that the unused and off-season Azorean green tea leaves (catechins-rich waste products) have potential antiradical activity that can be used for food and cosmetics preservation.